Book trade in the digital age: the role and advantages of online platforms - Akhmedova, Iroda; Mukhamedjonova, Zukhra; Mukhamedjonova, Fotima; Ravshanova, Nafisa (MMIT Proceedings, 2025)
This article explores the role of modern bookstores in online commerce, emphasizing the development of e-commerce platforms and the ongoing digital transformation within the book industry. The study examines approaches to systematizing bookstore operations and effectively organizing online platforms, highlighting aspects such as user convenience, AI-driven personalization, logistics, cataloging, and data analytics. Furthermore, it analyzes strategies for meeting the demand for less popular yet relevant books through the application of the “long tail” model. Drawing on research findings and statistical data, the article outlines current trends in the online book market and assesses the future prospects and advantages of digital bookstore formats.